Visual Outcomes After Sequential Posterior Chamber Phakic IOL with Corneal Refractive Surgery (Bioptics) for the Treatment of Myopic Astigmatism - Moshirfar M; Thomson RJ; West WB Jnr; McCabe SE; Sant TM; Shmunes MH; Ronquillo YC; Hoopes PC (Clinical Ophthalmology, 2020)
Majid Moshirfar,1– 3 Robert J Thomson,4 William B West Jnr,5 Shannon E McCabe,1,6 Thomas M Sant,5 Margaret H Shmunes,7 Yasmyne C Ronquillo,1 Phillip C Hoopes1 1Hoopes Vision Research Center, Hoopes Vision, Draper, UT, USA; 2John A. Moran Eye Center, Department of Ophthalmology and Visual Sciences, University of Utah School of Medicine, Salt Lake City, UT, USA; 3Utah Lions Eye Bank, Murray, UT, USA; 4McGovern Medical School at the University of Texas Health Science Center at Houston, Houston, TX, USA; 5University of Utah School of Medicine, Salt Lake City, UT, USA; 6Mission Hills Eye Center, Pleasant Hill, CA, USA; 7Burrell College of Osteopathic Medicine, Las Cruses, NM, USACorrespondence: Majid MoshirfarMD Hoopes Vision Research Center, Hoopes Vision, Draper, UT 84020, USATel +1 801-568-0200Fax +1 801-563-0200Email cornea2020@me.comPurpose: To report the outcomes of sequential posterior chamber phakic intraocular lens (PC-pIOL) with corneal refractive surgery in conventional (PC-pIOL prior to refractive surgery) and reverse (refractive surgery prior to PC-pIOL) bioptics for treating high myopic astigmatism.Setting: Tertiary refractive center, Draper, Utah, USA.Design: Retrospective case series.Methods: Medical records of patients who underwent planned bioptics were reviewed. Surgery involved PC-pIOL placement using an implantable collamer lens (ICL) with preceding or subsequent LASIK or PRK. Pre- and postoperative manifest spherical equivalent (SEQ), visual acuity, and PC-pIOL vault were analyzed.Results: Of the 51 eyes present at 12 months postoperatively, 49 eyes (96%) achieved target SEQ within ± 1.00 D and an identical amount achieved refractive astigmatism ≤ 1.00 D. Post-bioptics eyes achieved a postoperative UDVA equal to or better than preoperative CDVA in 45 eyes (88%). Efficacy and safety indices were 1.08 ± 0.20 (41 eyes) and 1.13 ± 0.22 (44 eyes) for conventional bioptics and 0.99 ± 0.42 (7 eyes) and 1.15 ± 0.38 (7 eyes) for reverse bioptics eyes at 12 months. The maximum PC-pIOL vault of conventional bioptics eyes (27 eyes) within 6 months before and after LASIK/PRK was 385 ± 159 μm and 377 ± 135 μm, respectively (P = 0.71).Conclusion: Bioptics for high myopic astigmatism was safe and effective. Reverse bioptics, although not as traditional, could provide similar results. Additionally, the PC-pIOL vault does not appear to be affected by LASIK/PRK.Keywords: bioptics, LASIK, PRK, posterior chamber phakic IOL, high myopic astigmatism, visual outcomes